التشكيل الفني للشخصية الساخرة "مسرحية الأقنعة المثقوبة أنموذجا لعز الدين جلاوجي - نبيلة, فرجان; جمال, مجناح (جامعة الوادي - University of Eloued, 2021)
تعد الشخصية المسرحية المنطلق والأساس في أعمال الأدباء وبؤرة الجدل في دراسات النقاد. فهي منبع للفرجة والدهشة والتشويق لدى القراء والمشاهدين واللبنة الأساس لمعمار البناء الدرامي. وغير خاف أن بناء الشخصية الساخرة يتطلب براعة في تصوير الشخصيات ورسم ملامحها وتحريكها في فضاء حافل بالمتناقضات والغرابة، فالمؤلف يخرجها من إطارها الواقعي ليشحنها بطاقات درامية وفكاهية، حيث يشتغل على السخرية في بناء شخصياته على ثلاثة أوجه: (سخرية صورية وسخرية لفضية وسخرية سلوكية ). ويتم ذلك وفق آليات فنية خاصة كالمفارقة، التلاعب اللفظي، التنابز بالألقاب، التناص. وهذا ما سعينا لتوضيحه باتخاذنا مسرحية الأقنعة المثقوبة حقلا للتطبيق، حيث تمكن المؤلف من تسخير هذه الأليات لكشف الزيف الاجتماعي والسياسي وإماطة الاقنعة وتقويم كل ما هو أعوج وبالتالي إيصال رسالته من جهة وإضفاء مسحة جمالية للنص وتحقيق المتعة الفنية للمتلقي من جهة اخرى. Abstract: The theatrical character is the starting point and the basis for the works of literature and the focus of the controversy in the studies of the ability to watch, surprise and suspense among readers and viewers and the building block of the architecture of the drama. It is quite clear that the construction of the satirical character requires a mastery in the photography of the characters and draws their features and moves them in a space full of contradictions and strangeness, the author takes them out of their realistic framework to energize them with dramatic and humorous powers where he works on the irony in building his characters on three sides (mock irony - silver and behavioral) This is done in accordance with the technical mechanisms, such as the paradox - verbal manipulation - the dissonance of the titles - and this is what we sought to explain by taking the play of “ the Perforated Masks” as a field of application where the author was able to use these mechanisms to detect the social and political falsification of the masks and to correct all that is crooked .Thus conveying the message on the one hand and giving the aesthetic tiding to the text and achieve the artistic pleasure for the receiver , on the other.
Keywords: السخرية ; المسرح ; المفارقة ; التناص ; الشخصية